Edukasi Osteoarthritis Pada Lansia Di Kelurahan Bunulrejo - Astuti, Sarita Sri; Multazam, Ali; Fransiska, Tri Dewi (Universitas Methodist Indonesia, 2024)
Osteoarthritis (OA) is a degenerative disease of the joints affected by the cartilage, joint lining, and bones which can cause joint pain and stiffness. OA can be caused by risk factors, namely age (aging process), gender, genetics, body weight, joint injury, and exercise. Disease development is usually slow but can ultimately cause joint failure with pain and disability. Osteoarthritis is ranked 12th in all diseases in the world with a high percentage of the population suffering from OA, namely 2.3% -11.3%. Method of implementing the activity was carried out on November 10 2023 in Bunulrejo Village, Malang City. The concept used in this activity is community-based participation. The target is all participants in the posyandu cadre meeting in Bunulrejo sub-district, 30 participants in promotional efforts in the form of physiotherapy education in the form of health promotion using leaflets as promotional media. This activity was carried out by giving a pre-test and post-test with questions given to participants at the posyandu cadre meeting in Bunulrejo sub-district. Objective counseling carried out to educate cadre meeting participants so that they can care about themselves regarding knee osteoarthritis and can carry out the exercises given during the counseling. Results showed an increase in understanding among cadre meeting participants regarding osteoarthritis. Conclusion Based on the outreach activities carried out in Bunulrejo Village on November 10 2023, it can be concluded that the event ran smoothly and was well realized. It is hoped that all of these outreach activities can increase the knowledge of the participants in the posyandu cadre meeting in Bunulrejo sub-district.